Adenoid cystic carcinoma of the uterine cervix. Report of six cases and review of the literature. - Bittencourt, Achiléa L.; Guimarães, Jorgete P.; Barbosa, Helenemarie S.; Carvalho, Walter A.; Lange, R. K. Uwe; Barata, A. Santos; Ramos, E. A. Gonçalves (Acta Médica Portuguesa, 1979)
Six cases of adenoid cystic carcinoma of the cervix were reported. Five of them were found among 1500 cervical biopsies. This frequency indicates that this tumor is more frequent than stated in the literature. In all cases the clinical data, colposcopic, cytological and histopathological findings, as well as the type of treatment and follow-up were reported. The paper points out that the cytology and colposcopy have characteristic features for the diagnosis. Because of the rarity of the tumor, the prognostic approach is not easily defined. The cases considered as stage II and III have poor prognosis, developing pulmonary metastasis as seen in one of our patients.